2022
DOI: 10.1371/journal.pone.0276661
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between trust and attitudes towards the COVID-19 digital contact-tracing app in the UK

Abstract: During the COVID-19 pandemic, digital contact-tracing has been employed in many countries to monitor and manage the spread of the disease. However, to be effective such a system must be adopted by a substantial proportion of the population; therefore, public trust plays a key role. This paper examines the NHS COVID-19 smartphone app, the digital contact-tracing solution in the UK. A series of interviews were carried out prior to the app’s release (n = 12) and a large scale survey examining attitudes towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…As of October 2021, less than a third of the UK population were estimated to have downloaded the COVID-19 app and it was acknowledged that some people were choosing to not use it ( Committee of Public Accounts, 2021 ). Findings from 1001 responders to the survey deployed by this research group found over half ( n = 511) had not downloaded the app, whom also had significantly lower trust than those who had downloaded the app ( Dowthwaite et al, 2022 ). It cannot be assumed that the public will use something because it has been developed with governmental or health services.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As of October 2021, less than a third of the UK population were estimated to have downloaded the COVID-19 app and it was acknowledged that some people were choosing to not use it ( Committee of Public Accounts, 2021 ). Findings from 1001 responders to the survey deployed by this research group found over half ( n = 511) had not downloaded the app, whom also had significantly lower trust than those who had downloaded the app ( Dowthwaite et al, 2022 ). It cannot be assumed that the public will use something because it has been developed with governmental or health services.…”
Section: Discussionmentioning
confidence: 88%
“…However, recent reports relating to problems implementing the new COVID-19 app ( Best, 2019 ) echoes back to the NHS not being capable of producing safe and reliable digital health care. Responses from the survey associated with these interviews showed higher trust was associated with perceived understanding, usefulness, and ease-of-use of the COVID-19 app ( Dowthwaite et al, 2022 ). Further work on understanding public adoption of the T&T app found a lack of understanding of how the app worked was highest in those who did not trust the app, and BAME communities had the lowest rates of uptake and use ( Dowthwaite et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…They also found that there were issues surrounding trust and understanding that hindered the effective adoption of the app. A follow-up analysis showed that there were statistically significant correlations between lower trust among nonusers, many aspects of the app, and the wider social and societal context [46]. A year after the app was launched, Pepper et al [2] identified 5 main themes during follow-up interview discussions: flaws in the app, usefulness and functionality affecting trust in the app, low trust in the UK government, varying degrees of trust in other stakeholders, and public disinterest.…”
Section: The Nhs Covid-19 Appmentioning
confidence: 99%
“…During the SARS‐CoV‐2 pandemic, smartphone‐based alert systems informed citizens about physical proximity to a later infected person. With this help of contact monitoring, app users could voluntarily take preventative measures and isolate themselves or get tested regularly to detect a potential infection and disrupt the transmission chain 53,54 . Similarly, time‐dynamic pollen and air quality maps, available on the smartphone, may be useful likewise the traffic navigation systems we use every day.…”
Section: Behavioral Impact Of the “Nose As Pollen Detector” Conceptmentioning
confidence: 99%
“…With this help of contact monitoring, app users could voluntarily take preventative measures and isolate themselves or get tested regularly to detect a potential infection and disrupt the transmission chain. 53,54 Similarly, time-dynamic pollen and air quality maps, available on the smartphone, may be useful likewise the traffic navigation systems we use every day. Patients may be induced to precisely prevent symptoms by avoiding times/places with high concentrations of the pollen to which they are allergic.…”
Section: F I G U R Ementioning
confidence: 99%